Health-related quality of life and its associated factors in Chinese middle-aged women. (3rd September 2018) - Huang, Y.; Chatooah, N. D.; Qi, T.; Wang, G.; Ma, L.; Ying, Q.; Lan, Y.; Song, Y.; Li, C.; Chu, K.; Chen, P.; Xu, W.; et al.
Abstract: Objective: The aim of this study was to compare health-related quality of life (HRQOL) by menopausal stage and investigate its associated factors in middle-aged Chinese women. Method: This was a cross-sectional, community-based study involving 868 participants aged 40–60 years in Gongshu District, Hangzhou, Zhejiang, PR China. HRQOL was assessed by the Short-Form Health Survey (SF-36). The menopausal symptoms and sociodemographic characteristics were surveyed. Results: The median (25–75th percentile) age of all participants was 51.24 (46.37–55.55) years. Differences were seen in domains of physical functioning, role-physical, bodily pain, general health and health transition by menopausal stage. The multivariate logistic regressions showed that there were associations between menopausal stage and HRQOL. Compared to premenopausal women, perimenopausal women had increased risks of having impaired functions in role-physical and health transition, and postmenopausal women were more likely to have impaired functions in physical functioning and health transition ( p < 0.05 for all). Menopausal symptoms were negatively associated with HRQOL. Being married or co-habiting tended to relate to better general health. Being unemployed or retired tended to be associated with impaired role-physical. Conclusions: There was a difference in HRQOL by menopausal stage in middle-aged Chinese women. Menopause might exert a negative impact on HRQOL, adjusting for menopausal symptoms and sociodemographic factors.